The neutrotime transcriptional signature defines a single continuum of neutrophils across biological compartments - Grieshaber-Bouyer, Ricardo; Radtke, Felix A.; Cunin, Pierre; Stifano, Giuseppina; Levescot, Anaïs; Nelson-Maney, Nathan; Blaustein, Rachel B.; Monach, Paul A.; Nigrovic, Peter A.; Aguilar, Oscar; Allan, Rhys; Astarita, Jilian; et al. (Nature Communications, 2021)
Neutrophils are implicated in multiple homeostatic and pathological processes, but whether functional diversity requires discrete neutrophil subsets is not known. Here, we apply single-cell RNA sequencing to neutrophils from normal and inflamed mouse tissues. Whereas conventional clustering yields multiple alternative organizational structures, diffusion mapping plus RNA velocity discloses a single developmental spectrum, ordered chronologically. Termed here neutrotime, this spectrum extends from immature pre-neutrophils, largely in bone marrow, to mature neutrophils predominantly in blood and spleen. The sharpest increments in neutrotime occur during the transitions from pre-neutrophils to immature neutrophils and from mature marrow neutrophils to those in blood. Human neutrophils exhibit a similar transcriptomic pattern. Neutrophils migrating into inflamed mouse lung, peritoneum and joint maintain the core mature neutrotime signature together with new transcriptional activity that varies with site and stimulus. Together, these data identify a single developmental spectrum as the dominant organizational theme of neutrophil heterogeneity.
CRIS-Team Scopus Importer:2023-10-02